O feminino na estética do corpo: uma leitura psicanalítica - Souza, Karina Carvalho Veras de (2007)
The aesthetics surgeries in the body, with frequency much more higher between the women and at the same time exalted significantly for the propaganda and the social context, has been configured currently as new way of expression to the feminine body. We question then, which significations are imputed to this body image, whose women submit aesthetics surgeries. In such a way, we objectify to analyze, from the psychoanalytic point of view: how the construction of the corporal image happens in the process of becoming woman; which problematical are disclosed by these women referring to the idealizations narcissists of this body and that way are configured in the feminine imaginary the cult to the body of the present time. According to this, we collected, simultaneously, some speech of women whom already have had submitted to such surgeries and after that we made an analysis of speech of these contents, in arder to chain in one comprehension psychoanalytic of the problematical now argued